Thermostabilized multiplex pcr assay for detection of selected bacteria associated with respiratory tract infections among malaysian hajj pilgrims - Noor, Nik Zuraina Nik Mohd (2020)
Respiratory tract infections (RTIs) are the commonest health problem during the annual Hajj pilrimage. Common bacteria associated with RTIs include Klebsiella pneumoniae, Haemophilus influenzae, Staphylococcus aureus, Streptococcus pneumoniae, Mycobacterium tuberculosis and Pseudomonas aeruginosa. Rapid detection of these pathogens could facilitate towards effective therapies. Therefore, this study aimed to develop and evaluate a thermostabilized polymerase chain reaction (PCR) assay for simultaneous detection of these six bacteria. The first step involved designing specific primers for the target bacteria and an internal amplification control (IAC). Each set of primers was evaluated to analyze for their specificity and sensitivity. A multiplex PCR was then developed by optimizing the concentration of primers and other components. Initial accuracy of the multiplex PCR was determined on clinical isolates. Subsequently, this assay had undergone lyophilization process in the presence of trehalose as the sugar-stabilizer. The assay stability was tested at different sets of temperature for different time-intervals. In the last stage, this assay was evaluated on the sputum specimens from Hospital USM and further evaluated at the field level using the specimens from Malaysian Hajj pilgrims. Results indicated that all the designed primers were specific to the respective target bacteria. The optimized concentrations of primers for bacteria (0.4 μM) and IAC (0.2 mM), MgCl2 (2.5 mM), dNTPs (0.2 mM) and Taq DNA polymerase enzyme (0.75 unit) were used in the development of multiplex PCR assay. Initial evaluation on bacterial isolates showed that the assay was 100% accurate on both target and non-target bacteria (n =145) (analytical specificity) with the lowest limit of detection was 10 pg DNA (200 bacterial cell) (analytical sensitivity). Lyophilization of this assay was successfully carried out in the presence of 6% trehalose in the PCR reagent. The assay was stable at the ambient temperature (25ºC) for at least six months. The sensitivity, specificity and accuracy of this assay were 100%, 92% and 95%, respectively on cinical sputum specimens (n = 200). Field evaluation on specimens from Malaysian Hajj pilgrims ensued the sensitivity and specificity of 100% and 92%, respectively, with the accuracy of 97%. From this study, two main bacteria detected from the clinical and Hajj sputum specimens were K. pneumoniae and H. influenzae, respectively. In conclusion, the rapidity, convenience, thermal-stable and reliable, could enable the application of this thermostabilized multiplex PCR assay to be used as a molecular diagnostic tool for the detection of six respiratory bacteria.